Producción audiovisual como herramienta de promoción turística para las quintas Juan León Mera y Juan Montalvo en la ciudad de Ambato - Hoyos Lozada, Johnny Alejandro (2024)
This project is based on the development of audiovisual pieces aimed at enhancing the historical knowledge of the Juan León Mera and Juan Montalvo Estates in Ambato and promoting them. Through a thorough and detailed search for information on these emblematic places, valuable insights were obtained. Based on interviews with professionals in the audiovisual field and product analysis, the most suitable type of production was identified. The resulting audiovisual products combine visual elements and immersive narrative, rescuing culture that is being lost over time, such as poetry, thus creating engaging and digestible educational content for the audience, while also highlighting the importance of these sites. These pieces not only promote the locations but also strengthen the preservation, especially of the intangible aspects of the estates. By deepening the understanding of the estates and their historical legacy, it is expected that these pieces will contribute to strengthening Ambato's cultural identity and promoting cultural tourism in the region, thus ensuring their legacy for future generations.